Travel Intelligence: Enhancing Counterterrorism and National Security - Anastasios-Nikolaos KANELLOPOULOS; Dimitrios STAVROPOULOS (Bulletin of "Carol I" National Defense University, 2024)
In the contemporary landscape of global security challenges, addressing the intricate dynamics of Counterterrorism and National Security is paramount. This paper emphasizes the pivotal role of Travel Intelligence (TRAVINT) in enhancing Counterterrorism (CT) strategy and improving security measures. Eventually, through a comparative analysis between theoretical frameworks and practical applications, supplemented by case studies of Hezbollah and Hamas, the study examines the significance of TRAVINT, in proactively identifying and preventing potential Terrorism and National Security.